ANALYSIS OF CIRCUMSTANCES ABUSE AROUND THE MEDAN CITY TRADITIONAL MARKET - Rahman, Rahman; Azmi, Karim; Hafiz Khuzairi, Ahmad; Sebayang, Zery Viandika; Hakim Nst, M. Irfan; Yusuf Khair, Ahmad (Proceeding International Seminar of Islamic Studies, 2023)
Traders selling on pedestrian paths (sidewalks/pedestrians) are a common phenomenon that we can see in big cities, a phenomenon that is often found on pedestrian paths/sidewalks in Indonesia is the misuse of the function of pedestrian paths or sidewalks by street vendors. This phenomenon is also widely seen in the city of Medan, we can see this in public areas such as parks, fields, and including traditional markets. This study aims to determine the extent to which people's perceptions of the existence of traders who use the road or sidewalk or pedestrian and the impact on road users. The research method used is descriptive with a quantitative approach. (Hanifah 2018). Respondents in this study were the surrounding community, buyers and traders using purposive sampling. The results show the existence of traders who, on the one hand, have a positive impact on the traders themselves, namely creating jobs and contributing to local governments. However, on the other hand, the negative impact is causing congestion for motorists and inconvenience for pedestrians using sidewalks. While the responses from road users themselves, although they feel uncomfortable and safe using the sidewalks, they understand that the existence of traders is a humane thing in order to make ends meet. So that we can again deny that pedestrians and traders are something that cannot be separated. On the other hand, we also have to think about how to accommodate pedestrian rights in using public spaces that are safe and comfortable, but also by not ignoring the interests of the general public who also have the same rights in accessing public spaces safely and comfortably.